1970
DOI: 10.1590/s0373-55241970000100001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution à l'etude des Serpulidae (Polychaeta Sedentaria) du Brésil

Abstract: Station Marine d'End01~me, Marseille 7 SME. 1763 à SME. 1830 : statÍons de prÍses benthi• ques au cours de la deuxieme partie de la campagne de la "Calypso" (janvier•février 1962), d'apres le carnet de bord établi par l'équipe de la Station Marine d'Endoume.Mus. 23 à Mus. 138: stations de p~~sespenthiques au cours de la premiere partie de la campagne de la "Calypso" (novembre 1961 -janvier 1962), voir la liste des stations publiée par FOREsT (1966). St. A à St. J: récoltes par J. LABoREL, M. KEMPF et l' Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
5

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 15 publications
1
38
0
5
Order By: Relevance
“…Caribbean Sea, from Florida to southern Brazil; in the Gulf of Mexico, it is only recorded from Alacranes Key (Ehlers 1887;Zibrowius 1970;ten Hove & San Martín 1995;. In this study, only one specimen of Pomatostegus stellatus was found on a fouling plate from Biscayne Bay, Florida (Fig.…”
Section: Distributionmentioning
confidence: 48%
See 4 more Smart Citations
“…Caribbean Sea, from Florida to southern Brazil; in the Gulf of Mexico, it is only recorded from Alacranes Key (Ehlers 1887;Zibrowius 1970;ten Hove & San Martín 1995;. In this study, only one specimen of Pomatostegus stellatus was found on a fouling plate from Biscayne Bay, Florida (Fig.…”
Section: Distributionmentioning
confidence: 48%
“…8) The differences between the species in Vermiliopsis are very tiny, and the morphological characters should be reviewed (Zibrowius 1970). Vermiliopsis multiannulata belongs to the V. infundibulum-complex, and V. annulata may include at least two species.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations